Death Does Matter—Cancer Risk in Patients With End-Stage Renal Disease: A Nationwide Population-Based Study With Competing Risk Analyses. Issue 3 (January 2016) - Weng, Shih-Feng; Chiu, Yu-Hsien; Jan, Ren-Long; Chen, Yi-Chen; Chien, Chih-Chiang; Wang, Jhi-Joung; Chu, Chin-Chen
Abstract : Abstract: Patients with end-stage renal disease (ESRD) have a high mortality rate. We hypothesized that not accounting for death as a competing risk overestimates the event rate caused by ESRD. Thus, we examined the cancer risk for patients with ESRD (ESRD Pos ) after death as a competing risk event had been adjusted for. Patients with newly diagnosed ESRD (n = 64, 299) between 1999 and 2007, together with age- and sex-matched controls without ESRD (ESRD Neg ) (n = 128, 592) were enrolled (1:2). In a Cox proportional hazards model that included death as a competing risk, ESRD Pos patients in Taiwan had a lower overall incidence (subdistribution hazard ratio [sdHR] = 1.29) of cancer than did ESRD Neg patients in a Cox model that did not include death as a competing risk (HR = 1.70). After competing mortality had been adjusted for, ESRD Pos patients ≥70 (sdHR = 0.82) and ESRD Pos patients on long-term dialysis (> 5 follow-up years, sdHR = 0.62), had a lower risk for developing cancer than did ESRD Neg patients. This finding supported our hypothesis that standard survival analyses overestimate the event rate, especially when the mortality rate is high. It also showed that ESRD Pos patients, when they grow older, were far less likely to develop cancer and far more likely to die because of underlying illnesses that might also affect the risk of death because of ESRD. Abstract : Supplemental Digital Content is available in the text